COMPARATIVE STUDY OF THE LEAD (II) REMOVAL FROM SIMULATED WASTEWATER USING GRANULAR ACTIVATED CARBON, RISE HUSK, AND SAW DUST - Younis Swadi Talaa (Journal of Engineering and Sustainable Development, 2016)
The adsorption of Pb (II) ions onto Granular Activated Carbon (GAC), Rise Husk (RH) and Saw Dust (SD) was investigated. The effect of pH, initial lead (II) concentration, dose of adsorbents, contact time and temperature were studied in batch experiments. The equilibrium data were analyzed using Langmuir, Freundlich and sips isotherm models at different doses of GAC, RH, and SD. The Langmuir model was found to fit the equilibrium data very well with high-correlation coefficient (R2). The maximum uptake capacities were found to be 6.823, 63.044, and 10.046 mg/g onto GAC, RH, and SD, respectively. Adsorption kinetic data were tested using pseudo-first-order, pseudo-second-order, and intra-particle diffusion models. The adsorption process was found to follow a pseudo-first order reaction. Thermodynamic parameters such as Gibbs free energy change, Enthalpy change and Entropy change have been calculated. These thermodynamic parameters indicated that the adsorption process was spontaneously under natural conditions and the adsorption was endothermic in nature. The study showed that locally available adsorbents, such as RH and SD, can be used as efficient adsorbents for the removal of lead (II) as compared with commercial GAC.